2016
DOI: 10.3109/00365521.2015.1132336
|View full text |Cite
|
Sign up to set email alerts
|

The impact of genetic factors on response to glucocorticoids therapy in IBD

Abstract: Glucocorticosteroids (GCs) are used for many years as first-line drugs for the achievement of remission in exacerbations of inflammatory bowel disease (IBD). However, close to 20% of patients are resistant to GCs, and 40% of patients become dependent on GCs. The challenge of today's personalized medicine is the anticipation of the steroid therapy effects even before the initiation of treatment. As several studies show, individually variable response to GCs in population has a genetic background and may depend … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
13
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 25 publications
(13 citation statements)
references
References 91 publications
0
13
0
Order By: Relevance
“…While glucocorticoids are effective to control exacerbations and induce remission of Crohn's disease in the majority of patients, approximately 20% of patients with Crohn's disease are resistant to glucocorticoids (Table ). Elevated Th17 cells and increased IL‐17A levels have been found in lesions of Crohn's disease .…”
Section: Wide‐ranging Glucocorticoid Sensitivity Of Diseases and Th17mentioning
confidence: 99%
“…While glucocorticoids are effective to control exacerbations and induce remission of Crohn's disease in the majority of patients, approximately 20% of patients with Crohn's disease are resistant to glucocorticoids (Table ). Elevated Th17 cells and increased IL‐17A levels have been found in lesions of Crohn's disease .…”
Section: Wide‐ranging Glucocorticoid Sensitivity Of Diseases and Th17mentioning
confidence: 99%
“…Variants in the remaining studied 7 genes that were studied (IL-1B, IL-2, IL-10, IL-4, JUN, CYP3A4, IPO13) did not meet these selection criteria and were not qualified for further analysis. Moreover, in the literature described in response to the GCS context, the loci in the NR3C1 (c.1184+646C>G and p.Asn767Asn), ABCB1 (c.2685+49T>C, p.Gly412Gly and p.Ile1145Ile) and TNF (c.-308G>A and c.-238G>A) genes were also included [11]. The highest average number of NGS reads (above 400×) was observed for variants p.Cys13Ser (rs61745470) and p.Met71Leu (rs8005905) of the HSPA4 and HSP90AA genes, respectively.…”
Section: Lr-pcr and Ngs Resultsmentioning
confidence: 99%
“…Although the reason for the differential response is multifactorial, including disease severity and complications, as well as environmental factors, it can be expected that the genetic component plays the most crucial role, which is estimated at up to 95% [9,10]. To date, most pharmacogenetic research on GCs has indicated the NR3C1 gene coding for the GCs receptor (GR) protein and the ABCB1 gene responsible for synthesis of the multidrug resistance protein 1a membrane GC efflux transporter whose overexpression results in decreased cytoplasmic GC concentration [11,12]. Fewer GC response studies also concern the participation of the FKBP5, TNF, and NLRP1 genes coding for co-chaperone 51 kDa FK506-binding protein (FKBP-51), tumor necrosis factor (TNF) and NACHT, LRR and PYD domain-containing protein 1, respectively [13][14][15][16].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…A review has proposed different markers associated with steroid therapy outcomes in patients with IBD 21. The most-studied molecule is the multidrug-resistant (MDR1) gene code for a drug efflux pump P-glycoprotein-170 (permeability glycoprotein or Pgp), which is expressed on the apical surface of lymphocytes and intestinal epithelial cells.…”
Section: Pharmacogenetics In Ibd Treatmentmentioning
confidence: 99%